Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Keputusan Pembelian pada GD. Printing dan Decal Design Toraja Utara Periode 2023-2024 - Valentino Sambo Pasau; Jens Batara Marewa; Helba Rundupadang (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The aim of this study: 1) To find out whether there is an influence on product quality regarding purchasing decisions at GD Printing and Decal Design, North Toraja, 2) To find out whether there is an influence of service quality on purchasing decisions att GD Printing and Decal Design, North Toraja. This type of research is quantitative research. The population in this research was 50 consumers. This sample in this research was 35 respondents using the accidental sampling method. This type of data used in this research is primary data, Primary data was obtained through filling out a questionnaire. The data analysis technique used is multiple linear regression testing using SPSS Version 25. The results of this research show that: 1) Product quality partially has a significant positive effect on purchasing decisions at GD Printing and Decal Design North Toraja, 2) Service quality does not partially influence purchasing decisions at GD Printing and Decal Design, North Toraja.